Faktor-Faktor Yang Memengaruhi Produktivitas Tenaga Kerja Di Indonesia - Maximilan Yan Lawa; Muana Nanga (Universitas Kristen Wira Wacana Sumba, 2012)
The objective of the study is to explore the impacts of human resource quality, province minimum wage, and unemployment rate toward labor productivity in Indonesia The study uses panel data that is combination of cross-section (33 provinces) and time-series data (2007-2010). In this study, panel data regression model is used and estimated by fixed effect model (FEM) and random effect model (REM). The result shows that human resource quality and unemployment rate have statistically significant effect on labor productivity in Indonesia, in which the former with positive sign and the later with negative. However, province minimum wage variable does not have significant effect on labor productivity.Key words: labor productivity, human resource quality, province minimum wage, unemployment rate, Indonesia